2017
DOI: 10.1111/jan.13282
|View full text |Cite
|
Sign up to set email alerts
|

Nurses’ response to parents’ ‘speaking‐up’ efforts to ensure their hospitalized child's safety: an attribution theory perspective

Abstract: These findings contribute to the understanding of antecedents that affect nurses' responses to parents' speaking-up initiatives: whether nurses will reject or heed the alert. Theoretical and practical implications for promoting parents' engagement in their safety are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 69 publications
0
7
0
Order By: Relevance
“…Each of these sources will trigger corresponding source effects. Source effects are best explained through attribution theory, which posits people make sense of the world by ascribing traits to, and establishing relationships between, the objects surrounding them (Fiske and Taylor, 1991;Kelley, 1967), particularly in provider-patient contexts (Bsharat and Drach-Zahavy, 2017). In evaluating a message, individuals typically draw on their inferences about the source's credibility and similarity (Wilson and Sherrell, 1993).…”
Section: Conceptual and Hypotheses Developmentmentioning
confidence: 99%
“…Each of these sources will trigger corresponding source effects. Source effects are best explained through attribution theory, which posits people make sense of the world by ascribing traits to, and establishing relationships between, the objects surrounding them (Fiske and Taylor, 1991;Kelley, 1967), particularly in provider-patient contexts (Bsharat and Drach-Zahavy, 2017). In evaluating a message, individuals typically draw on their inferences about the source's credibility and similarity (Wilson and Sherrell, 1993).…”
Section: Conceptual and Hypotheses Developmentmentioning
confidence: 99%
“…The expectation of this initiative is to provide immediate feedback to prevent human errors before harm occurs (Okuyama, Wagner, & Bijnen, 2014). Despite the potential benefits in error prevention, issues arise as to what extent healthcare workers, patients and families/parents engage with and respond to this initiative (Bsharat & Drach-Zahavy, 2017).…”
Section: Perceptions Of 'Speaking Up For Hand Hygiene' Among Healthcamentioning
confidence: 99%
“…Perceptions of speaking up may vary, based on: (1) the context of 'Speak Up'™ (i.e., medication error, hand hygiene), (2) the roles (i.e., healthcare workers, patients, families/parents), and 3the settings (i.e., adult, paediatric/neonatal). These factors could become barriers for collaboration (Bellissimo-Rodrigues et al, 2016;Bsharat & Drach-Zahavy, 2017). A study that explored the perception of patients and their involvement in speaking up for safety found that patients had a positive experience.…”
Section: Perceptions Of 'Speaking Up For Hand Hygiene' Among Healthcamentioning
confidence: 99%
See 2 more Smart Citations